Proceso de ASC - INTELIGENCIA ARTIFICIAL: NUEVAS TENDENCIAS EN EL DERECHO PROCESAL (2020)
The following study was conducted with the objective of evaluating the application of artificial intelligence in the judicial process, aiming to find a tool that could contribute to reducing congestion in the administration of justice. This led to the identification that a significant percentage of the cases handled by civil judges are executive processes. Therefore, it is proposed that some stages of these processes could be developed through artificial intelligence, particularly through the automation of certain phases.